High permselectivity hyperbranched polyester/polyamide ultrathin films with nanoscale heterogeneity. Issue 17 (11th April 2017) - Kong, Xin; Qiu, Ze-Lin; Lin, Chun-Er; Song, You-Zhi; Zhu, Bao-Ku; Zhu, Li-Ping; Wei, Xiu-Zhen
Abstract : Incorporating hyperbranched polyesters into a cross-linked polyamide matrix by interfacial polymerization to construct an ultrathin film with high permselectivity performance. Abstract : Membranes with both high permeability and selectivity are desirable for practical separation. In this work, three hyperbranched polyesters (HPEs) with different numbers of hydroxyl-terminated groups and molecular structures were, respectively, incorporated into a polyamide film formed by the interfacial reaction between the mixtures of HPE/piperazine (PIP) and trimesoyl chloride (TMC) on PVC hollow fiber substrates to endow the corresponding thin film composite (TFC) membranes with different permselectivity performances. The successful incorporation of HPEs into the cross-linked polyamide matrix and their gradient distribution in the corresponding selective layer were confirmed by ATR-FTIR and XPS analyses. Moreover, the permeation experiments for the fabricated TFC membranes revealed that HPEs most likely existed within the network or/and aggregate pores of the polyamide matrix due to their nanometer sizes and flexible molecular structures. Both the changes in the pore structures and the increase in the hydrophilicity of the polyamide matrix with the introduction of abundant hydroxyl groups pending in the HPE molecules led to the permeate flux of the TFC membrane increasing significantly. Importantly, nearly spherical H40 HPEs with intramolecular cavities could act as a molecular sieve to endow the selective layer with a high rejection capability. Meanwhile, the H40/PIP selective layer with a more negatively charged surface exhibited a higher rejection for SO4 2− ions while maintaining a low rejection for Cl − ions. These findings encourage further exploration of a new alternative material with such structures like HPE by interfacial polymerization to construct an ultrathin barrier film with high permselectivity performance.